Effects of High-Resolution Natural Sound with Inaudible High-Frequency Components on Healing, Symptoms, and Sleep Satisfaction in Terminally Ill Cancer Patients - Yasutaka Shimotsuura; Keisuke Ishizuka; Takashi Kawaguchi; Kazue Umetsu; Mariko Harada; Yujiro Inoue; Emi Kubo; Kazuhiro Kosugi; Takashi Igarashi; Seiya Enomoto; Hidehiko Taniyama; Tetsuo Iwata; et al. (Palliative Medicine Reports)
Objectives: This study aimed to assess the effects of high-resolution natural sound with inaudible high-frequency components (HNIH) on healing, symptoms, sleep satisfaction, and autonomic nerve function among terminally ill cancer patients. Methods: We conducted a single-arm, open-label study of 4-hour HNIH for 20 terminally ill cancer patients. We evaluated the healing state, symptoms (Japanese version of the Edmonton Symptom Assessment System-Revised, ESAS-r-J), global impression, and heart rate variability at 30 minutes (T2) and 4 hours (T3) after starting HNIH and sleep satisfaction the next morning (T4). Results: A total of 18 participants were evaluated (mean age: 69.4 years; 33.3% female). Post-intervention, there was a nonsignificant increase in Healing Scale scores at T2 (mean difference: 5.3, 95% confidence interval [CI]: −1.2 to 11.8, p = 0.106), but a significant increase at T3 (mean difference: 6.6, 95% CI: 1.0 to 12.3, p = 0.024). Specific ESAS-r-J scores demonstrated significant improvements in anxiety (mean difference at T2: −1.2, 95% CI: −1.99 to −0.34, p = 0.008; T3: −1.2, 95% CI: −1.99 to −0.34, p = 0.008), tiredness (mean difference at T2: −0.6, 95% CI: −1.18 to −0.04, p = 0.037), and shortness of breath (mean difference at T2: −1.0, 95% CI: −1.72 to −0.28, p = 0.010). Moreover, 66.7% of participants reported improved general conditions at T2 and T3, whereas 50% reported enhanced sleep satisfaction at T4. Heart rate variability analysis revealed a decreased low-frequency/high-frequency ratio in 55.6% of participants at T2 and 44.4% at T3. Conclusions: The present single-arm study showed that HNIH potentially enhanced healing, alleviated symptoms such as anxiety, tiredness, and shortness of breath, and improved sleep satisfaction in terminally ill cancer patients.